(untitled) (Causa: Jurnal Hukum dan Kewarganegaraan, 2025)
The development of information technology and the rapid growth of digital trade in Indonesia have created various challenges in the national taxation system. Cross-border digital transactions and the presence of foreign entities operating domestically require regulatory reforms to suit the dynamics of the digital economy. The results of this study confirm that unclear policies and limited data access have hampered the effectiveness of taxation, such as Value Added Tax (VAT) from digital transactions which was recorded at IDR 9.66 trillion until 2022 but has not been optimal, because many business actors have not been registered as taxpayers. In addition, gaps in tax provisions and minimal integration of administrative systems are major obstacles in ensuring taxpayer compliance and digital transaction data collection. This study also highlights the impact of digital tax policies on consumer behavior, especially the younger generation who are more sensitive to price changes due to the implementation of new rates in digital products and services. The implications of this policy adjustment not only increase state revenues, but also have the potential to increase public fiscal literacy and ensure fiscal justice in the midst of a digital pandemic. Therefore, legal reform and the development of innovative taxation models such as the Digital Service Tax and the "economic presence" approach are important to address these challenges in a sustainable and adaptive manner.